Inspection of working hours - How National Port State Control in the Baltic Region control working hours - Holmberg, Jerker (My University, 2012)
Work and rest hours are a hot topic at the moment, recent research has shown that the hours on watch has a significant effect on the fatigue among the seafarers, and that tired seafarers cause more accidents. This report aims to find out how the control of the working hours onboard ships are conducted in the EU-countries surrounding the Baltic Sea and what differences there are between the various countries. The report finds that there are similarities as to how the different countries perform the inspections due to that all countries follow the guidelines established by the Paris MoU organization.
Keywords: Transport; Transportteknik och logistik; Juridik och samhälle; Transport; Transport Systems and Logistics; Law and Society